Controlling Factors, Accumulation Model and Target Zone Prediction of the Coal‐bed Methane in the Huanghebei Coalfield, North China. Issue 4 (October 2014) - Lv, Dawei; Chen, Jitao; Li, Zengxue; Zheng, Guiqiang; Song, Cuiyu; Liu, Haiyan; Meng, Yanru; Wang, Dongdong
Abstract The Huanghebei Coalfield, one of the coal production bases in North China, was considered as a coalfield without coal‐bed methane (CBM) during past decades. In recent years, however, CBM has been discovered in coal‐bearing successions. In order to understand the CBM geological characteristics and accumulation process in this area, fifteen coal samples were collected and analyzed with respect to coal maceral and reflectance. The result shows that the gas distribution is uneven and the content varies in different areas even for the same coal bed. The storage of CBM is affected by geological factors such as burial depth, geological structures, and magmatic intrusion, among which the former two are more important in the formation of CBM. Deep burial of coal beds with the presence of cap‐rock mudstone can seal CBM. The CBM is also accumulated and preserved at the place where normal faults are distributed. Magmatic intrusion causes contact metamorphism and controls the CBM formation by heating the coal‐bearing successions. The obtained data indicate the geological conditions in northeastern Zhaoguan Mine are preferable for CBM formation and conservation; recent exploration estimates the CBM geological reserves up to 282.16 Mm3 and average of reserve abundance at 0.1662 × 108 m3 km−2. The Changqing Mine is a potential prospect in terms of CBM exploration since its geological conditions (structures and burial depth) are similar to the Zhaoguan Mine and its cap rock is even better.